Barriers to Prevention and Treatment of Type 2 Diabetes Mellitus Among Outpatients in Belarus - Sachkouskaya, Anastasiya; Sharshakova, Tamara; Kovalevsky, Dmitry; Rusalenko, Maria; Savasteeva, Irina; Goto, Aya; Yokokawa, Hirohide; Kumagai, Atsushi; Takahashi, Jumpei (Frontiers in Clinical Diabetes and Healthcare, 2022)
Objectives This study aimed to determine the main barriers and reasons for non-adherence to preventive measures and treatment for type 2 diabetes mellitus among outpatients in Belarus. Methods An anonymous questionnaire survey was conducted with 814 adults aged 18 years and over who visited outpatient health care units and hospitals in Belarus. The questionnaire was developed to analyze the perceived barriers that limit adherence to preventive measures and treatment for type 2 diabetes. Results The proportion of respondents who reported doing daily physical activity was 53.2%, and 46.6% consumed at least 400 grams of fruit and vegetables per day. Among the 42.8% of respondents with a prescribed treatment for type 2 diabetes mellitus, 50.1% sometimes forgot to take their medicine. The specific barriers to treatment most frequently identified by survey respondents were “Financial situation” (23.5% of respondents), and “Fear of side effects” (25.2%). Those for lifestyle instructions were “Insufficient knowledge” (29.3%), “Financial situation” (27.9%), and “Lack of motivation” (21.7%). Conclusions The study revealed that the main barriers to adherence were insufficient knowledge of diabetes and its treatment and an underestimation of the role of behavioral risk factors in health, combined with financial difficulties. We recommend that physicians should take a patient-centered approach to raising awareness of behavioral risk factors for type 2 diabetes mellitus, and suggest that the importance of adhering to preventative measures and treatment should be promoted in consultations in Belarus.